2012
DOI: 10.1556/oh.2012.29378
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian Diet and Nutritional Status Survey – The OTAP2009 study. IV. Macroelement intake of the Hungarian population

Abstract: Focusing on marcroelements, high sodium/salt intake represents the highest public health risk. The implementation of STOP SALT! National Salt Reducing Programme, i.e. decrease the salt content of processed food and provide proper information to the population about excessive salt consumption, should result in a beneficial change of salt intake and ameliorate the public health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…For elderly women (age ≥ 65 years), salt intake was also higher (11.7 and 11.3 g/day), and potassium intake was lower (2.6 and 2.5 g/day) in 2009 and 2014, respectively, compared with the daily 9.9 g of salt and 2.8 g of potassium intake recorded in the present study for elderly (age > 60 years) women. Consequently, the sodium/potassium ratio in the present study was more favorable than that obtained in national diet surveys [24,25]. In this comparison, we considered that, unlike the samples in the national diet surveys, our sample was not representative of the Hungarian elderly population; nevertheless, the methods and analysis tools we used were very similar (3-day dietary record, same method and software for data cleaning and processing).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For elderly women (age ≥ 65 years), salt intake was also higher (11.7 and 11.3 g/day), and potassium intake was lower (2.6 and 2.5 g/day) in 2009 and 2014, respectively, compared with the daily 9.9 g of salt and 2.8 g of potassium intake recorded in the present study for elderly (age > 60 years) women. Consequently, the sodium/potassium ratio in the present study was more favorable than that obtained in national diet surveys [24,25]. In this comparison, we considered that, unlike the samples in the national diet surveys, our sample was not representative of the Hungarian elderly population; nevertheless, the methods and analysis tools we used were very similar (3-day dietary record, same method and software for data cleaning and processing).…”
Section: Discussionmentioning
confidence: 75%
“…Our public information campaign took place in 2010. The analysis of the National Diet and Nutrition Status Survey in 2009 revealed that among the processed foods, bread, meat products, and preserved vegetables and pickles account for 36%, 21% and 10% of salt intake, respectively [25]. The high salt intake from bread prompted a negotiation with the Hungarian Bakers' Association, and a pledge to gradually reduce the salt content of bread by 16% from 2012 to 2017 was signed.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were processed by a computer programme (NutriComp), based on the Hungarian Nutrient Database. This work was a part of the National Nutrition and Nutritional Status Survey (OTÁP2009), details of which were published elsewhere MARTOS et al, 2012aMARTOS et al, , 2012bSARKADI NAGY et al, 2012). For the correction of sampling error and lack of response error post weighting has been applied.…”
Section: Dietary Intake Assessmentmentioning
confidence: 99%
“…Az OTÁP2014 vizsgálat az ötödik [1][2][3][4] nagy orszá-gos táplálkozási felmérés Magyarországon. Bár a megvalósult vizsgálatok módszertanilag némileg különböztek egymástól, céljuk ugyanaz volt -a lakosság táplálkozásá-ból fakadó kockázati tényezők minél pontosabb feltárása és az évek során bekövetkező változások nyomon köve-tése.…”
unclassified